From Asymmetry to Satisfaction: The Dynamic Role of Perceived Value and Trust to Boost Customer Satisfaction in the Tourism Industry - Ibrahim A. Elshaer; Alaa M. S. Azazz; Sameh Fayyad; Abdulaziz Aljoghaiman; Eslam Ahmed Fathy; Amr Mohamed Fouad (Tourism and Hospitality)
The study investigates how information asymmetry affects customer satisfaction in the tourism industry by examining trust and perceived value as mediating factors. The research implements an integrated model to test and prove information asymmetry’s direct and mediating effects on customer satisfaction by examining the literature gap. The research used a quantitative approach based on opinion polls distributed to 408 customers of hotels, tourism companies, and travel agencies who were in Egypt. SmartPLS 3 software implemented the data analysis process using partial least squares structural equation modeling (PLS-SEM). Previous studies have developed scales to measure information asymmetry and its related constructs, including customer trust, perceived value, and customer satisfaction. Multiple tests showed that the measurement tools possess both reliability and validity. Results strongly support all hypotheses: information asymmetry demonstrated significant direct negative effects on customer satisfaction (β = −0.187), trust (β = −0.520), and perceived value (β = −0.453). Conversely, customer satisfaction received significant positive direct effects from both trust (β = 0.273) and perceived value (β = 0.263). Importantly, trust (indirect effect β = −0.142) and perceived value (indirect effect β = −0.119) acted as powerful mediators, confirming that information asymmetry diminishes satisfaction largely by eroding these crucial factors. Crucially, the results demonstrate that the negative impact of information asymmetry on customer satisfaction is significantly mediated jointly through two parallel pathways: the erosion of customer trust and the impairment of perceived value. The research adds theoretical support to information asymmetry theory with its findings while also extending trust theory, perceived value theory, and expectancy disconfirmation theory in the field of e-commerce. E-commerce entities must establish clear communication to gain customer trust and create perceived value that helps compensate for information asymmetry to create enhanced customer loyalty and superior market position.